Reducing harm and promoting recovery through community-based mutual aid: Characterizing those who engage in a hybrid peer recovery community organization. (November 2019) - Ashford, Robert D.; Brown, Austin M.; Dorney, Georgeanne; McConnell, Nancy; Kunzelman, Justin; McDaniel, Jessica; Curtis, Brenda
Abstract: Background: Peer-based support services are often used within harm reduction organizations, and more recently within recovery community organizations (RCO). Identifying the characteristics of individuals who engage with these novel RCOs is needed. Additionally, conducting collaborative research with communities of people who use drugs (PWUD) or are in recovery is an effective and rewarding approach that allows individuals to take ownership and play a critical role in the study. Methods: This exploratory study employs a community-based participatory research (CBPR) framework in partnership with a peer-led hybrid recovery community organization, Rebel Recovery, in Florida. Peer staff participated in all phases of the study, helping to inform the study protocol, data collection, analysis, interpretation, and results write-up. A cross-sectional survey instrument was used to collect consumer intake data. Pearson Chi-square tests and multivariate binomial logistic regressions were used to examine relationships between consumer characteristics and service utilization. Results: Consumers (n = 396) of Rebel Recovery peer support services had a mean age of 35.60 years (SD = 9.74). Many were experiencing homelessness (35.4%), unemployed (69.7%), high school graduates or GED holders (68.2%) and had a last year income of less than $10, 000 (58.3%). The majority were users of heroin primarily (70.7%), with intravenous use being the preferred route of administration (63.9%). Exploratory analysis found that gender, marital status, and involvement in the child welfare system were significantly related to primary substance of use. Past 30-day engagement in recovery meetings had several statistically significant predictors including primary substance of use, age, housing status, annual income level, past-30-day arrests, tobacco use, and alcohol harm perception. Process findings from the CBPR methods used reconfirm the value of including peers in research involving PWUD and individuals in recovery. Conclusions: Results suggest that peer-based support services at a hybrid recovery community organization can successfully engage populations that are often underserved (i.e., experiencing homelessness, involved in drug court, intravenous users, etc.). Significant relationships identified in the exploratory analysis suggest that additional education concerning overdose and the potential benefits of recovery meetings may be useful for specific consumers. Additionally, several recommendations and benefits of engaging in community-based participatory research with peer-led organizations are made for future research. Highlights: Community-based participatory research involving peers is viable and effective. Hybrid RCOs primarily engage populations often underserved by other systems. Participant characteristics are associated with primary substance used and engagement.